Foliar application of sodium hydrosulfide (NaHS), a hydrogen sulfide (H2S) donor, can protect seedlings against heat stress in wheat (Triticum aestivum L.) - Min YANG; Bao-ping QIN; Xue-li MA; Ping WANG; Mei-ling LI; Lu-lu CHEN; Lei-tai CHEN; Ai-qing SUN; Zhen-lin WANG; Yan-ping YIN (Journal of Integrative Agriculture, 2016)
Temperature extremes represent an important limiting factor to plant growth and productivity. Low concentration of hydrogen sulfide (H2S) has been proven to function in physiological responses to various stresses. The present study evaluated the effect of foliar application of wheat seedlings with a H2S donor, sodium hydrosulfide (NaHS), on the response to acute heat stress. The results showed that pretreatment with NaHS could promote heat tolerance of wheat seedlings in a dose-dependent manner. Again, it was verified that H2S, rather than other sulfur-containing components or sodion derived from NaHS solution, should contribute to the positive role in promoting wheat seedlings against heat stress. To further study antioxidant mechanisms of NaHS-induced heat tolerance, superoxide dismutase (SOD, EC 1.15.1.1), catalase (CAT, EC 1.11.1.6) and ascorbate peroxidase (APX, EC 1.11.1.11) activities, and H2S, hydrogen peroxide (H2O2), malonaldehyde (MDA), and soluble sugar contents in wheat seedlings were determined. The results showed that, under heat stress, the activities of SOD, CAT, and APX, H2S, H2O2, MDA, and soluble sugar contents in NaHS-pretreated seedlings and its control all increased. Meanwhile, NaHS-pretreated seedlings showed higher antioxidant enzymes activities and gene expression levels as well as the H2S and soluble sugar levels, and lower H2O2, MDA contents induced by heat stress. While little effect was detected in antioxidant enzymes activities and soluble substances contents in pretreated wheat seedlings compared with its control under normal culture conditions (data not shown). All of our results suggested that exogenous NaHS could alleviate oxidative damage and improve heat tolerance by regulating the antioxidant system in wheat seedlings under heat stress.